Osmotic fragility of erythrocytes of some Nigerian species of domestic ruminants - Olusanya, S.K.; Adepoju, F.O. (1979)
Osmotic resistance of erythrocyte in hypotonic saline was spectrophotometrically determined in White Fulani cattle, West African Dwarf sheep and goats.Osmotic fragility was found to be highest in goat with maximum resistance occuring at 0.75% and 0.55% sodium chloride solutions. It was lowest in White Fulani cattle in which they occured at 0.55% and 0.35% of saline respectively. That of sheep was midway between those of cattle and goats, with minimum and maximum resistance occuring at 0.65% and 0.45% of saline. Erythrocyte osmotic fragility was influenced by red cell volume as measured by the mean corpuscular volume (MCV) of the species studied. Goat had the lowest MCV value of 21.40µ³, followed by sheep with 32.05µ³, and cattle with a value of 46.85µ³. This indicated that the smaller the size of a red cell, the lower its resistance to osmotic lysis in hypotonic solution.